Vienna Convention on the Law of Treaties : a commentary - e; Schmalenbach, Kirsten (Berlin : Springer, 2018)
The Commentary on the Vienna Convention on the Law of Treaties provides an in-depth article-by-article analysis of all of the Vienna Convention's provisions. Each provision's analysis consists of (I) Purpose and Function of the Article, (II) Historical Background with Negotiating History, (III) Elements of the Article and finally (IV) Treaties of International Organizations. In short, the present Commentary contains a comprehensive legal analysis of all aspects of the international law of treaties. Furthermore, where the law of treaties reaches into other fields of international law, e.g. the law of state responsibility, the relevant interfaces are discussed and contextualized. With its focus on international practice, the Commentary is an invaluable reference for both academia and practitioners of international law.
Part I Introduction -- Part II Conclusion and Entry into Force of Treaties: Conclusion of Treaties -- Reservations -- Part III Observance, Application and Interpretation of Treaties: Observance of Treaties -- Application of Treaties -- Interpretation of Treaties -- Treaties and Third States -- Part IV Amendment and Modification of Treaties -- Part V Invalidity, Termination and Suspension of the Operation of Treaties: General Provisions -- Invalidity of Treaties -- Termination and Suspension of the Operation of Treaties -- Procedure -- Consequences of the Invalidity, Termination or Suspension of the Operation of a Treaty -- Part VI Miscellaneous Provisions -- Part VII Depositaries, Notifications, Corrections and Registration -- Part VIII Final Provisions.
Includes bibliographical references and index.
Keywords: Vienna Convention on the Law of Treaties -- (1969 May 23); Treaties; Vienna Convention on the Law of Treaties (1969 May 23); Treaties